1999
DOI: 10.1055/s-2007-993830
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hypertrophic Cardiomyopathy in the Newborn Following Multiple Doses of Antenatal Corticosteroids

Abstract: Postnatal exposure to steroids has been associated with hypertrophic cardiomyopathy (HCM) in the newborn. Such an effect has not been described in infants born to mothers who received antenatal steroids. We report three newborns whose mothers were treated with betamethasone prenatally in different doses, duration of time, and who developed various degrees of HCM diagnosed by echocardiography. There was no maternal evidence of diabetes except for one infant whose mother had a normal fasting and post-prandial bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 7 publications
0
27
0
6
Order By: Relevance
“…26). Several studies have suggested that exogenous glucocorticoids also impact fetal heart development, producing cardiac enlargement (10,23,36,62). Cardiac enlargement is also observed with maternal Cushing's disease (19), and with highdose steroid treatment in infants with congenital adrenal hyperplasia (3,52).…”
mentioning
confidence: 99%
“…26). Several studies have suggested that exogenous glucocorticoids also impact fetal heart development, producing cardiac enlargement (10,23,36,62). Cardiac enlargement is also observed with maternal Cushing's disease (19), and with highdose steroid treatment in infants with congenital adrenal hyperplasia (3,52).…”
mentioning
confidence: 99%
“…10 An earlier case series described significant septal IVS and posterior wall LVPW hypertrophy in 3 neonates after multiple courses of prenatal corticosteroid treatment. 21 All abnormal findings resolved spontaneously within 6 months. One of those 3 infants was born to a mother with poorly controlled gestational diabetes mellitus, however, and another was one of triplets, which makes it difficult to attribute the findings to corticosteroid treatment alone.…”
Section: Discussionmentioning
confidence: 93%
“…An imbalance between protective mechanisms and matemai steroid levels may allow excessive transplacental passage of steroids. Hypertophic cardiomyopathy has been re-ACTA P/EDIATR 93 (2004) ported in premature infants given repeated antenatal courses of steroids (6) or postnatal dexamethasone to prevent or treat hronchopulmonary dysplasia (7,8). Dexamethasone is a synthetic glucocorticoid that readily crosses the placenta.…”
Section: Discussionmentioning
confidence: 99%